Defining the Doctorate in Africa: Aligning Purpose with Context - McKenna, Sioux; Onyango, Patrick (International Higher Education, 2025)
<h3 id="a-rapid-rise-in-doctoral-education-across-the-african-continent-has-occurred-without-sufficient-engagement-as-to-the-purposes-of-a-doctorate-the-assumption-that-the-doctorate-drives-the-knowledge-economy-is-evident-in-national-policies-implicitly-or-explicitly-but-there-is-neither-interrogation-of-this-supposedly-causal-relationship-nor-deliberation-as-to-how-the-doctorate-might-be-positioned-as-a-common-good-in-postindependence-countries" data-pm-slice="1 1 []">A rapid rise in doctoral education across the African continent has occurred without sufficient engagement as to the purposes of a doctorate. The assumption that the doctorate drives the knowledge economy is evident in national policies, implicitly or explicitly, but there is neither interrogation of this supposedly causal relationship, nor deliberation as to how the doctorate might be positioned as a common good in postindependence countries.